Incorporation of Pleurotus sajor-caju powder in cinnamon biscuit: study on nutritional, physical, colour and sensorial properties - Ng, S. H; Wan Amir Nizam, W.A.; Wan Rosli, W. I. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Discovery of novel dietary fibre (DF)-rich food ingredient is of great interest to meet the rising consumer demand for healthy food. Intake of DF-enriched food has been positively associated with a decreased risk of chronic diseases. Pleurotus sajor-caju (PSC), one of the prominent edible mushrooms widely cultivated in Malaysia, is useful for its culinary and medicinal purpose. This study aimed to determine the nutritional, physical, colour and sensorial properties of cinnamon biscuit formulated with PSC powder as partial replacement (0, 4, 8 and 12%) for wheat flour. Results indicated that elevated incorporation levels of PSC powder significantly (P<0.05) increased nutritional values of cinnamon biscuits; with 12% PSC cinnamon biscuit recorded the highest DF (9.84%), protein (7.85%) and ash (1.00%) content. In texture profile analyses, slight increment in firmness and reduction in crispiness of the cinnamon biscuits were detected with increasing levels of PSC powder. PSC-enriched cinnamon biscuits were reported to have lower L* value (ranged from 65.49 to 69.25) compared to control cinnamon biscuit (70.84), indicating darker surface colour. In comparison to control cinnamon biscuit, incorporation of PSC powder up to 8% produced higher scores in term of aroma, colour and appearance. In summary, incorporation of 8% PSC powder could be an effective way to develop nutritious cinnamon biscuit without jeopardizing its desirable physical and sensorial properties.